A novel hybrid propulsion system configuration and power distribution strategy for light electric aircraft. (15th June 2021) - Li, Shuangqi; Gu, Chenghong; Zhao, Pengfei; Cheng, Shuang
Highlights: Fuel cell and battery hybrid propulsion system topology for light electric aircraft. Adaptive power distribution strategy for aircraft with the hybrid propulsion system. An electric aircraft: Alpha Electro is used to validate the presented methodology. Fuel cell is protected from peak power outputs and efficiency is improved by 7.63%. Aircraft dynamic performance is improved by using hybrid propulsion technology. Abstract: Similar to the electrification of the automotive industry, the growing concerns with the shortage of fossil fuels has also called for a paradigm shift in aviation industry. To promote the aviation electrification process, it is necessary to develop an efficient energy storage system and a stable power transmission system to improve the reliability and extend the endurance of electric aircraft. This paper designs a novel propulsion system topology and power distribution algorithm for light manned electric aircraft. Firstly, a novel aircraft hybrid propulsion system topology is designed, in which the battery energy storage system can work synergistically with the fuel cell to provide power to the aircraft electric engine. Then, an adaptive energy management framework is developed to distribute the aircraft power requirement between energy storage devices. Meanwhile, an aircraft power balance state recognizer is designed to enhance the dynamic performance of the aircraft and adjust the working state of the propulsion system. The proposed hybrid propulsion system configuration and power distribution algorithm are verified under a prototype two-seater electric aircraft: Alpha Electro. Numerical analysis results indicate that the developed methods can dynamically meet the power requirement of aircraft under fast-charging and peak power requirement scenarios. With the developed hybrid propulsion system, most of the fuel cell high-power working points are moved to the medium and low area, which indicates that the fuel cell is effectively protected. Furthermore, the quantified hydrogen consumption can be reduced by 7.63% comparing to fuel cell electric aircraft.